Climate protection, resource efficiency, and sustainable engineering : transdisciplinary approaches to design and manufacturing technology - Horwath, Ilona; Schweizer, Swetlana (Science studies., 2023)
"The big societal challenges, such as climate change and public health, call for innovative approaches to address them. The contributors of this book present new ways to tackle these challenges by inter- and transdisciplinary collaborations in light weight engineering. They introduce a framework for transdisciplinary collaboration, explore the potential of light weight engineering in the areas of climate protection, resource efficiency, and sustainable mobility. To do so, they exemplify results and limitations of transdisciplinary collaboration based on three case studies: the optimization of rescue tools, the re-design of products to foster re-use and recycling processes in companies and society, and the additive manufacturing of individualized assistive tools and prostheses." --